(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article highlights important issues in improving the methodology for developing basic competencies of primary school teachers. The article analyzes the content of basic competencies, its components, and the professional skills required of teachers in the process of primary education. At the same time, the effectiveness of innovative teaching methods, interactive methods, and modern technologies that serve to develop competencies is substantiated.